Behavioral Differences in the Upper and Lower Visual Hemifields in Shape and Motion Perception - Zito, Giuseppe A.; Cazzoli, Dario; Müri, René M.; Mosimann, Urs P.; Nef, Tobias (Frontiers in Behavioral Neuroscience, 2016)
Perceptual accuracy is known to be influenced by stimuli location within the visual field. In particular, it seems to be enhanced in the lower visual hemifield for motion and space processing, and in the upper visual hemifield for object and face processing. The origins of such asymmetries are attributed to attentional biases across the visual field, and in in the functional organization of the visual system. In this paper we tested content-dependent perceptual asymmetries in different regions of the visual field. 25 healthy volunteers participated in this study. They performed three visual tests involving perception of shapes, orientation and motion, in the four quadrants of the visual field. The results of the visual tests showed that perceptual accuracy was better in the lower than in the upper visual field for motion perception, and better in the upper than in the lower visual field for shape perception. Orientation perception did not show any vertical bias. No difference was found when comparing right and left visual hemifields. The functional organization of the visual system seems to indicate that the dorsal and the ventral visual streams, responsible for motion and shape perception, respectively, show a bias for the lower and upper visual hemifields, respectively. Such a bias depends on the content of the visual information.